2016
DOI: 10.18632/oncotarget.12795
|View full text |Cite
|
Sign up to set email alerts
|

MCM10 overexpression implicates adverse prognosis in urothelial carcinoma

Abstract: Urothelial carcinoma (UC) occurs in the upper urinary tract (UTUC) and the urinary bladder (UBUC). The molecular pathogenesis of UC has not been fully elucidated. Through data mining of a published transcriptome of UBUC (GSE31684), we identified Minichromosome Maintenance Complex Component 2 (MCM2) and MCM10 as the two most significantly upregulated genes in UC progression among the MCM gene family, the key factors for the initiation of DNA replication. To validate the clinical significance of MCM2 and MCM10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Previous studies have observed MCM10 is overexpressed in different types of human cancers, such as medulloblastoma, cervical cancer, and esophageal cancer . Furthermore, Li et al demonstrated that MCM2 and MCM10 were the two most significantly upregulated genes in urothelial carcinoma progression among the MCM gene family . However, the functional roles and prognostic values of MCM10 remained largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have observed MCM10 is overexpressed in different types of human cancers, such as medulloblastoma, cervical cancer, and esophageal cancer . Furthermore, Li et al demonstrated that MCM2 and MCM10 were the two most significantly upregulated genes in urothelial carcinoma progression among the MCM gene family . However, the functional roles and prognostic values of MCM10 remained largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show MCM10 is often dysregulated under pathological conditions . Genetic amplification and/or overexpression of MCM10 were also observed in different types of human cancers . For instance, Cheng et al found a series of replicative helicase proteins, such as MCM10, MCM2, MCM4, MCM5, and MCM6 were overexpressed in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MCMs may mediate DNA damage repair. Knockdown of MCM genes was reported to significantly inhibit cell proliferation [50,57,58]. Based on the biological and functional significance of MCMs, many MCM-targeted drugs have been developed.…”
Section: Mcms As Diagnostic Markers and Therapeutic Targetsmentioning
confidence: 99%
“…These observations raise the possibility that MCM10 might be closely associated with tumorigenesis. Several lines of evidence have shown the important roles of MCM10 in several malignant tumors . Al‐Ejeh et al also indicated that MCM10 was deregulated in triple negative breast cancer and might hold therapeutic potential in aggressive breast tumors.…”
Section: Introductionmentioning
confidence: 99%